Uso de ultrassom na produção de salame tipo italiano - Alves, Larissa de Lima (2016)
The aim of this study was to evaluate the effect of ultrasound application (US, bath 25 kHz, 500 W) on physical, chemical and microbiological properties of Italian-type fermented sausage during processing and storage. The US was used after mass stuffing in synthetic packaging during 0 min, 3 min, 6 min and 9 min of application. Completely randomized design was adopted (DIC) and the data submitted to analysis of variance (ANOVA) to test the significance of the variables. Further, a Pearson´s correlation analysis was performed and the differences among the averages were calculated by using the Tukey s test (p≤0.05). Some data were subjected to multivariate analysis of variance (MANOVA), complemented by the technique of principal components analysis. The parameters of fermented sausage evaluated included counts of lactic acid bacteria (Pediococcus pentosaceus and Pediococcus acidilactici) and Microccocaceae (Staphylococcus xylosus and Staphylococcus carnosus), aw, pH, color (CIE L * a * b *), lipid oxidation (peroxide value and TBARS ), protein oxidation (thiol), total heme pigments, non-heme iron and metmyoglobin, during processing (days 0, 2, 15 and 28) and along the shelf-life (after 1, 30 and 120 days). Texture parameters (cohesiveness, flexibility, chewiness and hardness) were evaluated in fermented sausages after 90 days of storage and the formation of volatile compounds at the beginning (day 1) and the end of storage (after 120 days). US had a positive effect on the growth of bacteria in some processing steps and storage conditions (p<0.05), especially on Micrococcaceae (Staphylococcus xylosus and Staphylococcus carnosus) with 9 min of US exposure. The pH, aw and color parameters were not significantly affected by the US (p>0.05). The oxidation of lipids and proteins was accelerated with US application, but maintaining acceptable values in the final product. The total heme pigments, non-heme iron and metmyoglobin were affected by sonication (p<0.05) and influenced the oxidative reactions and vice versa. The canonical discriminant analysis separated the samples into groups according to the day of evaluation and not according to the treatments. Therefore, due to the predominant effect of processing time / storage in fermented sausage characteristics a lack of significant effect of sonication time was observed. The US did not significantly affect texture profile parameters (p>0.05), but hardness and chewiness tended to reduce with sonication. Regarding the volatiles were no statistical differences between treatments (p>0.05), except for ethanol and hexanol (p<0.05) at the beginning of storage. The US has affected the growth curve of bacteria, accelerating or inhibiting their growth that some points, and has the potential to be explored in improving the texture and red color formation of fermented sausages. The lack of pronounced effect on US some characteristics was primarily attributable to acoustic parameters adopted, low exposure time to the US, fermented sausage consistency, mass heterogeneity and quantity / fat composition, among other factors. Thus, it is suggested to further studies to assess the potential of using the US as emerging technology in the fermented sausage manufacturing.